RNA m5C methylation: a potential modulator of innate immune pathways in hepatocellular carcinoma - Meng, Sun; Jiangtao, Bai; Haisong, Wang; Mei, Li; Long, Zhou; Shanfeng, Li (Frontiers in Immunology, 2024)
RNA 5-methylcytosine (m 5 C) methylation plays a crucial role in hepatocellular carcinoma (HCC). As reported, aberrant m 5 C methylation is closely associated with the progression, therapeutic efficacy, and prognosis of HCC. The innate immune system functions as the primary defense mechanism in the body against pathogenic infections and tumors since it can activate innate immune pathways through pattern recognition receptors to exert anti-infection and anti-tumor effects.Recently, m 5 C methylation has been demonstrated to affect the activation of innate immune pathways including TLR, cGAS-STING, and RIG-I pathways by modulating RNA function, unveiling new mechanisms underlying the regulation of innate immune responses by tumor cells. However, research on m 5 C methylation and its interplay with innate immune pathways is still in its infancy. Therefore, this review details the biological significance of RNA m 5 C methylation in HCC and discusses its potential regulatory relationship with TLR, cGAS-STING, and RIG-I pathways, thereby providing fresh insights into the role of RNA methylation in the innate immune mechanisms and treatment of HCC.Keywords：RNA m5C methylation，TLR, cGAS-STING, RIG-I，hepatocellular carcinoma